Total versus near-total thyroidectomy in Graves’ disease and their outcome on postoperative transient hypoparathyroidism: study protocol for a randomized controlled trial? - Maschuw Katja; Schlosser Katja; Lubbe Dirk; Nies Christoph; Bartsch Detlef (Trials, 2012)
Abstract Background Graves’ disease is an independent risk factor for transient postoperative hypoparathyroidism. Besides the disease itself, preparation techniques are influential. Transient postoperative hypoparathyroidism has severe consequences for patients’ physical and psychological state. It can be life threatening during the acute phase and may impair patients’ health, psyche and quality of life thereafter. For the surgical therapy of Graves’ disease, total thyroidectomy is recommended according to the national S2-guideline. The evidence- based on a metaanalysis- is criticized by the Cochrane diagnostic review commentary for substantial methodological deficits. Two randomized controlled trials lead to the hypothesis that a near-total resection with bilateral remnants of ≤ 1g on each side compared to total thyroidectomy will significantly reduce the occurrence of transient postoperative hypoparathyroidism with equal therapeutic safety. Methods/Design Patients with Graves’ disease indicated for definite surgery are eligible for the trial. Trial-specific exclusion criteria are: conservative treatment, malignancy, previous thyroid surgery and coincident hypoparathyroidism. The trial is created for therapeutic purpose through process innovation. It is designed as a prospective randomized controlled patient and observer blinded multicentered trial in a parallel design including an active comparator and an intervention group. The intervention addresses the surgical procedure: near-total thyroidectomy leaving bilateral remnants of ≤ 1g on each side in the intervention group and total thyroidectomy in the control group. The occurrence of transient postoperative hypoparathyroidism is defined as primary endpoint. Secondary endpoints are: reoperations due to bleeding, recurrent laryngeal nerve palsy, permanent hypoparathyroidism, recurrent disease, changes of endocrine orbitopathy and quality of life within a one-year follow-up period. The primary efficacy analysis follows the intention-to-treat principle. A binary logistic regression model will be applied. Complications and serious adverse events will be descriptively analyzed. Discussion The trail is expected to balance out the shortcomings of the current evidence. It will define the surgical gold standard for the surgical therapy of Graves’ disease. Patients’ safety and quality of life are assumed to be enhanced. Therapy costs are likely to be reduced and health care optimized. The conduction of the trial is feasible through the engagement and commitment of the German association of endocrine surgeons and the National Network for Surgical Trials. Trial registration German clinical trials register (DRKS) DRKS00004161